Antioxidant Activity of Nanoemulsion Gel of Rambutan Fruit Peel Extracts (Nephelium lappaceum L.) Using Dpph and FTC Method - Muhtadi, M; Hartanto, Riyan Eko; Wikantyasning, Erindyah Retno (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Rambutan fruit peel extracts had been reported to have quite high antioxidant activity. There are several compounds classes of phenolic and flavonoid contained in Rambutan fruit peel extracts such as ellagic acid, corillagine and geraniine that are responsible for its antioxidant activity. Antioxidant compounds are commonly used in cosmetic preparations. This study was conducted to explain the antioxidant activity of rambutan fruit peel extracts in nanoemulsion gel formulation which was tested with DPPH (1.1-diphenyl-2-picrylhydrazyl) and FTC (Ferric Thiosyanate) method. A method of DPPH was done by making 5 series of concentration and read as absorbance at λ max by using spectrophotometer UV-Vis and for the method of FTC, it was read as absorbance at λ 500 nm. The result of absorbance could be used to determine the value of IC50 (DPPH method) and inhibition percent (FTC method). The result of the study using DPPH method obtained the IC50 values of nanoemulsion gel of Rambutan fruit peel extracts in the amount of 9.32 ± 0.06 mg/mL, which was higher than X® Sunscreen Gel and vitamin E with IC50 value of 40.41 ± 0.98 mg/mL and 10.41 ± 0.05 mg/mL, respectively. The results with the FTC method obtained the percent value of inhibition of 51.09 ± 0.99%, which was lower than X® Sunscreen Gel and vitamin E with percent value of inhibition of 60.07% ± 13.23% and 79.07 ± 7.62%, respectively. These results indicated that Rambutan fruit peel extracts had quite high antioxidant activity that after they were formulated into a nanoemulsion gel.